Estudo morfométrico do canal do hipoglosso - Silveira, Camila Augusto [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The hypoglossal nerve (HN) is responsible for the intrinsic and extrinsic muscles of the tongue. Knowledge of this is extremely important because this nerve is responsible for tongue movement. HN paralysis can be associated to the disease itself in various zones in which the NH travels, mainly the hypoglossal canal (HC). Variations in shape of the hypoglossal canal have been pointed to as the cause of HN paralysis in several studies. Four hundred dried intact human skulls without sex or race identification, belonging to the Discipline of Anatomy of ICTSJC – UNESP were studied. Each canal was classified into types: type I (without division in the HC), type II (HC with low bone spike), type III (HC more than two projections bone), type IV (presence of complete bony bridge without dividing HC into two distinct canals) and type V (presence of bone bridge by dividing into two HC canals). HC was found in 100% of skulls studied in both side. Regarding types, we found 538 (67.25%) hypoglossal canal of type I (34%, right side and 33.25%, left side), 108 (13.5%) of type II (7.38%, right side, and 6.13%, left side), 60 (7.5%) hypoglossal canal of type III (3.5%, right side and 4.0%, left side) 84 (10.5%) of type IV (4.75%, right side and 5.75%, left side) and 5 (0.63%) of the type V (0.13%, right side and 0.5%, left side). We found 5 (0,63%) different HC and classified ourselves in type VI, VII and VIII. The average angle was 51,3º on right side and 50,25º on left side. Detailed knowledge of the anatomy of the CH supports professionals in interventions of bloody skull base and also in giving the correct diagnosis of the probable causes of paralysis of the hypoglossal nerve

O nervo hipoglosso (NH) é o nervo responsável pelo controle da musculatura intrínseca e extrínseca de língua. Seu conhecimento é de extrema importância uma vez que ele é responsável pela motricidade da língua. Paralisias do NH podem estar associadas a doenças no próprio NH ou serem decorrentes de alterações nas várias regiões por onde o NH transita, principalmente o canal do hipoglosso (CH). Variações na forma do CH e septações no seu interior têm sido apontadas como causa de paralisias do NH. Em 400 crânios secos íntegros (800 lados) da Disciplina de Anatomia do ICTSJC – UNESP o CH foi classificado quanto à incidência, o lado, tipo e angulação do CH. Cada canal do hipoglosso foi classificao em tipos: tipo I (CH sem divisão); tipo II (CH com pequena espícula óssea); tipo III (CH com mais de duas projeções ósseas); tipo IV (presença de ponte óssea completa sem dividir o CH em dois canais distintos) e tipo V (presença de ponte óssea dividindo o CH em dois canais). O CH foi encontrado em 100% dos crânios estudados, bilateralmente. Com relação aos tipos, encontramos 538 CH (67,25%) do tipo I (34% LD e 33,25% LE), 108 CH (13,5%) do tipo II (7,38% LD e 6,13% LE), 60 CH (7,5%) do tipo III (3,5% LD e 4,0% LE), 84 (10,5%) do tipo IV (4,75% e 5,75% LE) e 5 CH (0,63%) do tipo V (0,13% LD e 0,5% LE).Encontramos 5 CH (0,63%) diferentes, denominados por nós como tipo VI, VII e VIII. A média geral das angulações foi de 50,19º para o LD e 50,75º para o LE. O conhecimento detalhado da anatomia do CH auxiliará os profissionais em intervenções cruentas na base do crânio e também no correto diagnóstico das prováveis causas da paralisia do nervo hipoglosso.
Keywords: Nervo hipoglosso; Anatomia; Lingua